Estructura y operacionalización de un modelo de autogestión para la fundación FUDIS Amigos del Mundo frente al cáncer - Guanín Tello, Ivonne Jacqueline (2009)
The present work is the "Structure and operationalization of a self-management model for the world FUDIS Friends Foundation against Cancer", using as an instrument a sequence of steps that make the foundation seek to find their own funding and achieve their development.